PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA APARATUR PEMERINTAH DAERAH, MELALUI KOMITMEN ORGANISASI DAN JRI SEBAGAI VARIABEL INTERVENING PEMKO LHOKSEUMAWE - Yusri Hamzi (Jurnal Akuntansi Muhammadiyah (JAM), 2013)
This research was conducted at Government Lhokseumawe . Samples were level officials on duty at 18 SKPK. The research method using a simple linear regression with one independent variable and two dependent variables. The sample using purposive sampling method and the data processed using SPSS version-16 is in the analysis of qualitative and quantitative methods. Objectives to be obtained in this study was to determine the effect of budgetary participation on the performance of local government officials, organizational commitment, and job relevance of information as an intervening variable. From the calculation that budgetary participation and organizational commitment did not significantly affect the performance of the apparatus. Results of regression testing participation with the value 0.274 or greater than 0.05. Likewise with the organization 's commitment to siqnifikan level of 0.047 and also greater than 0.05. Unlike the case with JRI, the test results obtained with siqnifikan level of 0.066 or less than 0.05.T-test results of the test showed a negative relationship with the performance of the apparatus, and unlike the case with the commitment of organizations that have a positive relationship. This means that with a high commitment to encourage the performance of local government officials Lhokseumawe . Keywords : Budget Participation, Apparatus Performance, Organizational   Commitment And Job Relevant   Information